The role of brand authenticity on social media for Fashion e-Tailers - Dias, Ana Cristina Correia (2019)
Brands increasingly use social media to interact with prospects and customers and communicate their distinctive attributes, in order to adequately position themselves in the marketplace. Meanwhile, consumers increasingly look for authenticity in products and brands, resorting to brand-related cues in marketing communications to make authenticity assessments. This dissertation investigated whether and how fashion e-tailers use brand authenticity cues in social media and their potential impact on audience response. To this end, a survey with 105 respondents was conducted to identify the level of perceived brand authenticity of four fashion e-tailers with significant brand activity on Facebook – Farfetch, mytheresa, MATCHESFASHION.COM, and Zalando – measured by Morhart et al.'s (2014) perceived brand authenticity scale. Based on survey results, two brands were selected – Farfetch and Zalando –, as they were perceived to be the most and the least authentic, respectively. Data was collected (n=201) about their use of authenticity cues on Facebook posts and corresponding consumer response from September to November 2018. The use of authenticity cues was measured using Morhart et al.'s (2014) listed cues and response was measured by the number of reactions, comments, and shares of each post. Results show that when controlling for brand and audience size, existential cues trigger users to comment on Facebook posts. Brands wanting to be perceived as authentic may emphasize and incorporate human attributes in their social media communications.